Biocarvão e vermiculita na produção de mudas de alface (Lactuca sativa L.) ebeterraba (Beta vulgarisL.) - Pinto, Gheysa Julio (2016)
This study aimed to evaluate the addition of biochar and vermiculite to organic compost (horse manure and crop residues of vegetable) in different particle sizes (G1 - < 0.05 mm and G2 - 2 0 to 4.0 mm) and six doses (5, 10, 20, 30, 40 and 50%) and how they affect the chemical (conductivity and pH), the physical (density, porosity, macroporosity and microporosity)atributes of the substrates prepared and the production of upper parts (MSPA), root (MSR) and total (MST) dry matter of lettuce (Lactuca sativa L.) and sugar beet (Beta vulgaris L.) seedlings.The lettuce seeds were Vanda - Sakata and Early Wonder - TopSeedPremimiun, for lettuce and beets, respectively. The experiment to determine the physical and chemical atributes of pure materials was conducted in a completely randomized design (CRD) with 5 treatments, 10 repetitions, for a total of 50 experimental units (containers with capacity for 100 cm3) and substrates prepared in 4 treatments, 6 doses, 10 repetitions, totaling 240 tubes. The test for seedling production was also conducted in CRD, the use of substrate prepared with 4 treatments, 6 doses, 10 repetitions, totaling 240 tubes for lettuce and 6 repetitions, totaling 144 tubes for beet seedlings. Statistical analysis of the data used the statistical software SISVAR, by means of grouping test (Scott-Knott) and SAS to run correlation test among the variables. The CG2-5, CG2-30, VG1-5 and VG1-10 for lettuce seedling production and CG1-30 to beet production were the best treatments.